A Conductive Polymer Hydrogel Supports Cell Electrical Signaling and Improves Cardiac Function After Implantation into Myocardial Infarct. Issue 8 (25th August 2015) - Mihic, Anton; Cui, Zhi; Wu, Jun; Vlacic, Goran; Miyagi, Yasuo; Li, Shu-Hong; Lu, Sun; Sung, Hsing-Wen; Weisel, Richard D.; Li, Ren-Ke
<x xml:space="preserve">Abstract</x> Background— Efficient cardiac function requires synchronous ventricular contraction. After myocardial infarction, the nonconductive nature of scar tissue contributes to ventricular dysfunction by electrically uncoupling viable cardiomyocytes in the infarct region. Injection of a conductive biomaterial polymer that restores impulse propagation could synchronize contraction and restore ventricular function by electrically connecting isolated cardiomyocytes to intact tissue, allowing them to contribute to global heart function. Methods and Results— We created a conductive polymer by grafting pyrrole to the clinically tested biomaterial chitosan to create a polypyrrole (PPy)-chitosan hydrogel. Cyclic voltammetry showed that PPy-chitosan had semiconductive properties lacking in chitosan alone. PPy-chitosan did not reduce cell attachment, metabolism, or proliferation in vitro. Neonatal rat cardiomyocytes plated on PPy-chitosan showed enhanced Ca2+ signal conduction in comparison with chitosan alone. PPy-chitosan plating also improved electric coupling between skeletal muscles placed 25 mm apart in comparison with chitosan alone, demonstrating that PPy-chitosan can electrically connect contracting cells at a distance. In rats, injection of PPy-chitosan 1 week after myocardial infarction decreased the QRS interval and increased the transverse activation velocity in comparison with saline or chitosan, suggesting improved electric conduction. Optical mapping showed increased activation in the border zone of PPy-chitosan–treated rats. Echocardiography and pressure–volume analysis showed improvement in load-dependent (ejection fraction, fractional shortening) and load-independent (preload recruitable stroke work) indices of heart function 8 weeks after injection. Conclusions— We synthesized a biocompatible conductive biomaterial (PPy-chitosan) that enhances biological conduction in vitro and in vivo. Injection of PPy-chitosan better maintained heart function after myocardial infarction than a nonconductive polymer.